2022
DOI: 10.1177/01614681221087304
|View full text |Cite
|
Sign up to set email alerts
|

Strong Equity: Repositioning Teacher Education for Social Change

Abstract: Background: Equity is invoked as a watchword in teacher education—a catch-all connected to an array of issues related to diversity, justice, or gaps in outcomes and opportunities for minoritized groups. This conceptual article argues that equity is often undefined and undertheorized in teacher education, and the complexities involved in addressing the structural inequalities of schooling are seldom acknowledged. Purpose: This article unpacks recurring themes in the discourse of equity and teacher education. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…Across the United States, many teacher education programs have equity-related goals, and/or they include the language of equity in mission statements or lists of program highlights. However, programs do not necessarily mean the same thing by the word, “equity,” and programs that publicly advertise their commitment to equity do not necessarily carry it out in program design or ways of evaluating teacher candidates or program impact (Cochran-Smith & Keefe, 2022). In contrast, the programs we highlight in this section are noteworthy in that they have reframed teacher education evaluation by “baking” equity into multiple program components, including curriculum, coursework and fieldwork, and assessment/evaluation practices.…”
Section: Equity-centered Teacher Education Evaluation: Promising Poli...mentioning
confidence: 99%
See 1 more Smart Citation
“…Across the United States, many teacher education programs have equity-related goals, and/or they include the language of equity in mission statements or lists of program highlights. However, programs do not necessarily mean the same thing by the word, “equity,” and programs that publicly advertise their commitment to equity do not necessarily carry it out in program design or ways of evaluating teacher candidates or program impact (Cochran-Smith & Keefe, 2022). In contrast, the programs we highlight in this section are noteworthy in that they have reframed teacher education evaluation by “baking” equity into multiple program components, including curriculum, coursework and fieldwork, and assessment/evaluation practices.…”
Section: Equity-centered Teacher Education Evaluation: Promising Poli...mentioning
confidence: 99%
“…As we elaborate below, our analysis found that most major policy proposals regarding teacher education evaluation and accountability said very little about equity. We concluded our policy analysis with a clarion call for teacher education evaluation/accountability centered in "strong equity" (Cochran-Smith et al, 2018;Cochran-Smith & Keefe, 2022), and we posed 11 guiding principles toward this end. We stand firmly by those principles.…”
mentioning
confidence: 98%
“…This example is significant in illustrating structural ableism and institutional cyclic oppression. Although social justice and equity are dominant ideologies in the field of teacher education, these themes are often employed rhetorically (Cochran-Smith & Keefe, this issue) but are not always wholly instantiated within the work of the program, such as in this example. This illustrates the program’s failure to ensure its social justice philosophy was at work in all aspects of the preparation program, and internally, to challenge assumptions and expectations about the role of a teacher.…”
Section: Deficit Discourse: Structural Ableism In Special Education T...mentioning
confidence: 99%
“…Again, the point here is not to police one another for political correctness, but to demonstrate real effort toward more equitable structures that are truly representative of the disability community that special education teacher preparation is so committed to, and better mirror the foundational values of teacher education. It is important to note that although using inclusive language is an important start, it is only one part of dismantling ableism within teacher education and one step toward embracing broader notions of justice and equity (Cochran-Smith & Keefe, this issue). Inclusive language may not hold power if companion structures, processes, and policies remain ableist and exclusionary.…”
Section: Democratic Discourse In Special Education Teacher Preparationmentioning
confidence: 99%
See 1 more Smart Citation